Dynamics Of Public Service Implementation Before, During And Post Pandemi Covid-19 In Palu City - Rahman, Arif; Syamsidar, Syamsidar; Royfandi, Moh. (Technium Social Sciences Journal, 2023)
This study aims to reveal phenomena related to public services in Palu City before, during and after the Covid-19 pandemic. This type of research is qualitative with a descriptive approach. As for the collection technique through library data, reading, processing, and recording research materials. The results of the study show that the three aspects of research, namely responsiveness, responsibility and accountability, still pose various problems in the process of public service. First, the slow response of the bureaucracy in receiving complaints, wishes, community needs in public services so that it has an impact on the community itself. Second, that public services are carried out not in accordance with existing norms, wherein Law No. 25 of 2009 concerning public services explains that the State must be active to participate in the social life of society, to provide whatever is best for the people, especially in service. Third, where all the interests of society are always contrary to the interests of the bureaucracy in the administration of public services. For example, the services that are carried out must be completed as quickly as possible according to the applicable mechanism, but the results of the research show that the services carried out are not in accordance with the norms and desires of the community.